Fish larvae species identification and population genetic structure of Boleophthalmus boddarti (Pallas, 1770) from selected mangrove sites in Peninsular Malaysia - Azmir, Izzati Adilah (2018)
A study on fish larvae species identification from mangrove areas of Pendas Johor, Matang Perak, Pekan Pahang and Setiu Terengganu and population genetic assessment of Blue-spotted mudskipper Boleophthalmus boddarti, from similar sampling areas except Setiu Terengganu has been done. The fish larvae collection occurred from April 2015 to September 2015 by using a bongo net, towed at a depth of about 0.5 m from the surface for 5 min against the tidal flow. The mudskipper was collected with casting nets, hand net and bare hands at night time and especially when the tide is low, in between the month of January 2016 and September 2016. This study aims to identify fish larvae to species level by adopting integrative method; a combination of comparative and molecular method. The composition, abundance, diversity and phylogenetic relationship among fish larvae samples were also investigated. The lack of species identification work on fish larvae in Peninsular Malaysia has warrant this study to be conducted. The status of genetic population of mudskipper B. boddarti is investigated using two markers, mitochondrial and microsatellite. Specific microsatellite loci for the B.boddarti are absent and information on population structure and phylogenetic relationship among B. boddarti populations are lacking. Therefore, this study was conducted to characterize the genetic structure of B. boddarti in Peninsular Malaysia through mitochondrial Cytochrome c Oxidase I (COI) gene and new set of microsatellite marker developed using Next Generation Sequencing (NGS) method. A total of 354 individuals of fish larvae were collected and through morphological analyses they were identified morphologically into 21 families, 20 genus and 18 species. Among the 21 families, the top 3 families, namely, Gobiidae (39.26%), Engraulidae (14.97%), and Clupeidae (14.40%), occurred in all sampling areas except in Setiu. The highest diversity of fish larvae was recorded for Pendas, Johor with Shannon Wiener index H = 2.699, and the lowest was for Setiu Terengganu with H = 0.832. Setiu Terengganu recorded the lowest evenness value, indicating high single-species dominance. From the total of 354 fish larvae collected, a representative of 177 fish larvae were selected and sequenced using Cytochrome c Oxidase I (COI) gene where they corresponded to 18 families, 33 genus and 41 species of larval fish. Results from BLAST and BOLDSYSTEM search showed all sequences have high percentage identity index and similarity (90% to 100%). The identification of fish larvae was mostly successfully confirmed through phylogenetics analysis showing monophyletic status between query sequences with reference sequences obtained from GenBank. However the Sillago vittata and Sillago sihama sequences was found to be in separate clusters despite their similar genus. A few strong match of specimens from different genus was found with high bootstrap value (n>90%) through Neighbour-Joining (NJ) and Maximum-likelihood (ML) analysis. The Paramugil parmatus was matched with Liza melinoptera (NJ =100%, ML = 99%) and Pseudogobius oligactis was matched with Eugnathogobius oligactis (NJ = 92%, ML 94%). A total of 11,957 short sequence repeats (SSR) motifs were identified via analysis of 6.87 Gb nucleotides conducted by using Illumina sequencing to produce a comprehensive transcript dataset for B. boddarti motif. The most abundant type of repeat motif was mono-nucleotide (63.66%), followed by tri-nucleotide (18.88%), di-nucleotide (15.54%), tetra-nucleotide (0.83%) and both penta- and hexanucleotide was found the least (0.11%). Experimental screening of 27 pairs of microsatellite primers detected 30% of microsatellite loci were polymorphic. Both markers showed strong genetic differentiation between populations with result from mitochondrial COI analysis revealed haplotype sharing between Pekan Pahang and Pendas Johor populations (KY754661) and Pendas Johor and Matang Perak populations (MF572075). Zero connectivity between Matang Perak and Pekan Pahang populations (Fst = 0. 53086); Nm was 0.44186) due to huge biogeographical barrier. Microsatellite marker analysis detected minimal differentiations (Fst) among Pendas Johor and Matang Perak populations (Fst=0.26461) and between Pekan Pahang and Matang Perak populations (Fst=0.38423, Nm=0.80129) reflecting isolation between populations. However the species was found to be locally adapted where genetic variation was more likely to occur within populations rather than among populations (ratio of 6:3). The mtDNA marker further showed no evidence of recent population expansion through Tajima’s D, Fu Fs’ and Bayesian skyline plots but possible occurrence in population expansion did occurred long before present years during Pleistocene era. High haplotype diversity (0.680 to 0.819) and moderate nucleotide diversity (0.00657 to 0.05886) was found from COI analysis showing genetic variation was in moderation even though Pendas Johor possessed highest number of sample. Thus this reflect possibility of environmental degradation and further supported by microsatellite marker analysis where moderate genetic variation was also seen (mean Ho = 0.4337, mean He = 0.4535). Deviated Hardy-Weinberg equilibrium was mainly due to heterozygote deficiencies and possibility of inbreeding especially in Pekan Pahang with small sample size (Izz 4-6, Ho = 0.280, He = 0.497). The high Ho compared to expected heterozygosity (He) value documented in Pendas Johor population particularly, signal recently bottleneck event showed through Wilcoxon test with probability value less than 0.05 after applying three mutational model (IAM, SMM and TPM) and Mode-Shift indicator further confirmed the population was under shifted mode. The population structure of B. boddarti inferred based on the two types of markers was not showing significant differences. In conclusion, integrative identification provide better results to phenotypically ambiguous specimen like the fish larvae and application of mitochondrial and nuclear gene markers were able to characterize genetic structure and evolutionary kinship of B. boddarti.